Enhancing fermentation quality and fiber decomposition of Phragmites australis silage by introducing Bacillus subtilis and lactic acid bacteria consortia - Liu, Yong; Zhang, Songbai; Liao, Junrui; Khan, Nazir Ahmad; Tang, Shaoxun; Zhou, Chuanshe; Tan, Zhiliang; Elnagar, Asmaa; Rehan, Ibrahim F.; Zigo, František; Salem, Abdelfattah Z. M. (Frontiers in Veterinary Science, 2025)
IntroductionAs a low-cost, high-fibre biomass resource, Phragmites australis (reed) has significant potential for feed applications, particularly as a partial replacement for conventional roughage in ruminant diets.MethodsThis study investigated the effects of integrating Bacillus subtilis (B. subtilis BNCC109047) with homofermentative/ heterofermentative lactic acid bacteria (LAB) consortia on the fermentation and nutritional quality of Phragmites australis (reed) silage. Five treatments were evaluated: a Control (CK, without inoculum) and four inoculants—LAB (1.5 × 108 CFU/kg LAB, 1:4 homofermentative (Lentilactobacillus plantarum BNCC 336421 and Pediococcus pentosaceus BNCC 135034 in a ratio of 1:1): heterofermentative (L. buchneri BNCC 187961) ratio), LAB-BS2.5 (LAB plus 2.5 × 107 CFU/kg B. subtilis), LAB-BS5.0 (LAB plus 5.0 × 107 CFU/kg B. subtilis), and LAB-BS10.0 (LAB plus 1.0 × 108 CFU/kg B. subtilis)—with triplicate samples per group. Silage fermentation was conducted for 90 days.ResultsLAB-BS10.0 demonstrated superior fermentation outcomes, achieving the highest lactic acid-to-total acid ratio (62.3%, p < 0.05) and the lowest ammonia nitrogen (NH3-N) content (0.60 ± 0.09 g/kg, p < 0.05). Acetic and butyric acid concentrations were significantly reduced (p < 0.05), while neutral detergent fiber (NDF) decreased by 5.9% compared to the Control. Ether extract (EE) increased to 4.76% (p < 0.01), highlighting enhanced lipid preservation.ConclusionThese results emphasize the synergistic potential of B. subtilis and LAB to optimize P. australis silage, providing a sustainable strategy to enhance forage quality and tackle global feed shortages.